A cost‐effective high‐throughput metabarcoding approach powerful enough to genotype ~44 000 year‐old rodent remains from Northern Africa. (20th July 2016) - Guimaraes, S.; Pruvost, M.; Daligault, J.; Stoetzel, E.; Bennett, E. A.; Côté, N. M.‐L.; Nicolas, V.; Lalis, A.; Denys, C.; Geigl, E.‐M.; Grange, T.
Abstract: We present a cost‐effective metabarcoding approach, aMPlex Torrent, which relies on an improved multiplex PCR adapted to highly degraded DNA, combining barcoding and next‐generation sequencing to simultaneously analyse many heterogeneous samples. We demonstrate the strength of these improvements by generating a phylochronology through the genotyping of ancient rodent remains from a Moroccan cave whose stratigraphy covers the last 120 000 years. Rodents are important for epidemiology, agronomy and ecological investigations and can act as bioindicators for human‐ and/or climate‐induced environmental changes. Efficient and reliable genotyping of ancient rodent remains has the potential to deliver valuable phylogenetic and paleoecological information. The analysis of multiple ancient skeletal remains of very small size with poor DNA preservation, however, requires a sensitive high‐throughput method to generate sufficient data. We show this approach to be particularly adapted at accessing this otherwise difficult taxonomic and genetic resource. As a highly scalable, lower cost and less labour‐intensive alternative to targeted sequence capture approaches, we propose the aMPlex Torrent strategy to be a useful tool for the genetic analysis of multiple degraded samples in studies involving ecology, archaeology, conservation and evolutionary biology.